Supercritical extraction as an effective first-step in a maize stover biorefinery - Attard, Thomas M.; Theeuwes, Elke; Gomez, Leonardo D.; Johansson, Emma; Dimitriou, Ioanna; Wright, Phillip C.; Clark, James H.; McQueen-Mason, Simon J.; Hunt, Andrew J. (Royal Society of Chemistry, 2015)
Supercritical carbon dioxide (scCO2) has been investigated for the generation of valuable waxy compounds and as an added-value technology in a holistic maize stover biorefinery. ScCO2 extraction and fractionation was carried out prior to hydrolysis and fermentation of maize stover. Fractionation of the crude extracts by scCO2 resulted in wax extracts having different compositions and melting temperatures, enabling their utilisation in different applications. One such fraction demonstrated significant potential as a renewable defoaming agent in washing machine detergent formulations. Furthermore, scCO2 extraction has been shown to have a positive effect on the downstream processing of the maize stover. Fermentation of the scCO2 extracted maize stover hydrolysates exhibited a higher glucose consumption and greater potential growth for surfactant (in comparison with non-scCO2 treated stover) and ethanol production (a 40% increase in overall ethanol production after scCO2 pre-treatment). This work represents an important development in the extraction of high value components from low value wastes and demonstrates the benefits of using scCO2 extraction as a first-step in biomass processing, including enhancing downstream processing of the biomass for the production of 2nd generation biofuels as part of an integrated holistic biorefinery.